Space Charge Dynamics in Epoxy Resins Under the Influence of a Long-Term High Electric Field at Various Temperatures - Zhang, Hongliang; Li, Kun; Jin, Hai; Li, Kangle; Li, Xiaonan; Liu, Peng; Peng, Zongren (Frontiers in Chemistry, 2022)
As the main insulating material of an ultra-high voltage (UHV) resin impregnated paper (RIP) bushing, epoxy resin accumulates space charge under the DC voltage, which would affect the insulation properties of the bushing. In this article, the evolution of space charge accumulation and dissipation within the epoxy resin samples was measured under the influence of a long-term (24 h) electric field of 60 kV/mm at 40°, 60°, 80°, and 100°C. The experimental results show that the space charge transport in the epoxy sample was a long-time dynamic process. When the temperature was not greater than 60°C, only homocharge accumulation was observed within the samples, and the space charge distribution did not reach a stable state even after 24 h of voltage application. When the temperature was not lower than 80°C, the positive heterocharge accumulation was observed at the interface between cathode and epoxy. Through analysis by fitting and numerical simulation, it was verified that the positive heterocharge accumulation was caused by the limitation of the hole extraction, and the transport of holes within the samples obeyed the jump conductance model.